Seiches in a conical lake of large semi-vertical angle - JANARDHAN, S. (MAUSAM, 1961)
The problem of seiche-oscillations in lakes having the shape of solids of revolution has been considered by Lamb for the particular case of a paraboloidal lake. This paper deals with a right conical lake of large semi-vertical angle, with and without a circular cylindrical coaxial island. The differential equation of seiche-oscillations, expressed in the vector form is solved by a variational method, first used by Hidaka for seiche-problems. Period equations have been obtained for those modes of vibration, involving nodal diameters and nodal circles. The results obtained for a laks with a central island are applied to Lake Toya, Japan.